Peran Pemeriksaan Handgrip Strength sebagai Sarana Skrining Risiko Penurunan Kekuatan Otot di Usia Produktif - Fadil Hidayat; Alexander HalimSantoso; Edwin Destra; Frilliesa Averina; Heri YantoPutra (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
Muscle strength decline is a factor that affects functional performance and work capacity in productive age. Handgrip strength is a practical method to detect this decline quantitatively. This activity aims to identify muscle strength status through handgrip strength examination and provide education on preventing muscle function decline. The examination was conducted on productive age individuals using a digital handgrip measuring tool. Data were collected from 49 participants, consisting of 25 men and 24 women. Handgrip strength values ​​were recorded and categorized into normal or weak status. Furthermore, participants received education through visual posters explaining the relationship between lifestyle, muscle strength, and productivity. The average handgrip strength in men was 36 kg (SD 8.75) and in women it was 22.94 kg (SD 9). The proportion of participants with weak muscle strength reached 10.20% in men and 12.24% in women. This examination successfully identified risk groups that had not shown any clinical symptoms previously. Handgrip strength examination is effective as an early screening tool for the risk of muscle strength decline in productive age. Education based on examination results can increase awareness and encourage lifestyle changes towards long-term muscle function maintenance.